A utilização da metodologia ativa Problem Based Learning e do Podcast na aprendizagem do componente curricular filosofia no ensino médio - DASSIE, Aline Moreno (2022)
The present research was developed in the Graduate Program (Master's Degree) in Education of the Universidade do Oeste Paulista (Unoeste), in the research line 2: Formation and action of the teaching professional and educational practices. The issue that guided the development of this study was: As the use of the active methodology Problem Based Learning (PBL) involving the resolution of everyday problems and philosophical themes that will be presented in a Podcast format, can students learn Philosophy in a more meaningful way? Based on this research issue, the general objective was drawn: To analyze the potential of the active methodology Problem Based Learning (PBL) and the podcast media as a pedagogical resource for learning the Philosophy component in High School, and the specific objectives: to analyze whether the learning of Philosophy is significant for students when using PBL; to investigate the challenges and the construction of skills and competences in the application of PBL in High School; build a podcast evidencing the progress of the PBL process and to analyze how philosophy learning is materialized in digital narratives through podcasts and comments on them as an educational resource in formal education. The characterization of the research was a qualitative approach, of the intervention type, with the participation of the philosophy teacher and 25 students from the third grade of high school at a public school in the interior of São Paulo. The instruments used for data collection were: a preliminary questionnaire with students, records made through Google docs, during the application of the seven steps of PBL, production and recording of podcasts and comments made to t hem. In addition, a self-assessment and peer assessment were carried out with the students, culminating in a round of conversation . An interview with the teacher was also carried out in order to analyze the process experienced. Data analysis was performed from two categories that emerged from the theoretical framework and data obtained: Category A - Potentiality of PBL in Philosophy teaching: the students` protagonism and collaborative work among peers; and Category B - The potential of Digital Information and Communication Technologies (DICT) in Philosophy learning: content production through podcast. It was evidenced that, in the application of PBL combined with the construction of a podcast, in the discipline of Philosophy, in High School, students exercised their protagonism and learned to work collaboratively with their peers. Regarding the learning of Philosophy, this was very relevant for the students, since very important themes about texts from two classics, such as the My th of the Cave, by Plato, and Education after Auschwitz, by Adorno, could be thought over with the students. inserted in the contemporary era. Thus, the results acquired throughout this study revealed the educational value that both PBL and the podcast have in the formation of students. It is hoped that this research can benefit the breakdown of barriers between the traditional and the innovative model in relation to learning and teaching.